The Influence of Mindfulness, Collective Values, Transformational Leadership, Working Conditions, Psychological Empowerment on Organizational Citizenship Behavior (OCB) Among High School Teachers in Medan - Meutia Nauly; Saut Purba; Ibrahim Gultom (RIRAI Publisher, 2022)
This study aims to obtain an OCB model for teachers in private and public schools. The model was developed based on a literature review on what factors can predict OCB. Based on the studies that have been carried out (attitude and personal factors, in this study mindfulness was used (personal with full attention). This research is a quantitative approach with a causal correlational type of research. This type of study is also described as a survey design, with data collection using a scale or research instrument through an online survey using the G Form from Google. The results showed that; (1) OCB could be effected directly by mindfulness and working condition, but not for the collective values; (2) Mindfulness has a direct effect on Transformational Leadership and working conditions; (3) Collective values don’t have effect on working conditions. So, it can be stated that mindfulness affects OCB through transformational leadership variables and working conditions. Similarly, it can be stated that collective values influence OCB through transformational leadership and working conditions. The implication of this study is to improve OCB in schools, it is necessary to pay attention to the various conditions that are prepared, in this case the strengthening of mindfulness, through training and practice of mindfulness implementation, and strengthening of working conditions, which also means that structural empowerment of teachers becomes necessary.